Temporal and spatial expression of genes involved in DNA methylation during reproductive development of sexual and apomictic Eragrostis curvula. Issue 1 (December 2017) - Selva, J.; Siena, L.; Rodrigo, J.; Garbus, I.; Zappacosta, D.; Romero, J.; Ortiz, J.; Pessino, S.; Leblanc, O.; Echenique, V.
Abstract Recent reports in model plant species have highlighted a role for DNA methylation pathways in the regulation of the somatic-to-reproductive transition in the ovule, suggesting that apomixis (asexual reproduction through seeds) likely relies on RdDM downregulation. Our aim was therefore to explore this hypothesis by characterizing genes involved in DNA methylation in the apomictic grassEragrostis curvula . We explored floral transcriptomes to identify homologs of three candidate genes, for which mutations inArabidopsis and maize mimic apomixis (AtAGO9/ZmAGO104, AtCMT3/ZmDMT102/ZmDMT105, andAtDDM1/ZmCHR106 ), and compared both their spatial and temporal expression patterns during reproduction in sexual and apomictic genotypes. Quantitative expression analyses revealed contrasting expression patterns for the three genes in apomictic vs sexual plants.In situ hybridization corroborated these results for two candidates, EcAGO104 andEcDMT102, and revealed an unexpected ectopic pattern for theAGO gene during germ line differentiation in apomicts. Although our data partially support previous results obtained in sexual plant models, they suggest that rather than an RdDM breakdown in the ovule, altered localization ofAtAGO9/ZmAGO104 expression is required for achieving diplospory inE .curvula . The differences in the RdDM machinery acquired during plant evolution might have promoted the emergence of the numerous apomictic paths observed in plants.